2006
DOI: 10.1016/j.bone.2006.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter and receptor expression in osteocytic MLO-Y4 cells

Abstract: Neurotransmitter regulation of bone metabolism has been a subject of increasing interest and investigation. We reported previously that osteoblastic cells express a functional serotonin (5-HT) signal transduction system, with mechanisms for responding to and regulating uptake of 5-HT. The clonal murine osteocytic cell line, MLO-Y4, demonstrates expression of the serotonin transporter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 51 publications
1
92
0
5
Order By: Relevance
“…Functional 5-hydroxytryptamine (5-HT) transporters and receptors are present in osteoblasts, osteocytes, and osteoclasts, and stimulation of these receptors influences bone cell activities [30,31]. Consistent with this, use of SSRIs, but not tricyclic antidepressants, was associated with increased rates of bone loss at the hip in older women [32] and men [33].…”
Section: Discussionmentioning
confidence: 89%
“…Functional 5-hydroxytryptamine (5-HT) transporters and receptors are present in osteoblasts, osteocytes, and osteoclasts, and stimulation of these receptors influences bone cell activities [30,31]. Consistent with this, use of SSRIs, but not tricyclic antidepressants, was associated with increased rates of bone loss at the hip in older women [32] and men [33].…”
Section: Discussionmentioning
confidence: 89%
“…24 One of the possible mechanisms by which antidepressant use may contribute to fracture risk is the effect that antidepressants could have on the microarchitecture of bone. 34 Also, the use of antidepressants has been associated with an increased risk of falling 35 and depression itself might also increase fracture risk. 36 Strengths of our study include its reasonable sample size and the duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological roles of 5-HT in osteoblasts have already been reported: for example, 5-HT potentiated the parathyroid hormone-induced increase in AP-1 activity in osteoblastic UMR106 cells (2). In a recent study by Bliziotes et al (2006), 5-HT was reported to stimulate the release of PGE 2 in clonal ostocytic MLO-Y4 cells (3). Their observation indicates that several kinds of osteoblast-like cells are endowed with some functional 5-HT receptors.…”
mentioning
confidence: 92%